Gambaran Bentuk Disiplin Peserta Didik di Kelas VII SMP N 1 Koto XI Tarusan - Joni Adison; Suryadi Suryadi (Journal on Education, 2022)
This research is motivated by the presence of students who are late for school, there are students who withdraw during school hours, there are students who don't dress neatly to school, there are students who often go in and out during school hours, there are students who wear colorful shoes to school. The purpose of this study is to describe: 1) The form of student discipline based on the authoritarian concept, 2) The form of student discipline based on the permissive concept, 3) The form of student discipline based on the concept of controlled freedom. This research is a quantitative descriptive study that seeks to describe a situation as it is. The population of this study was all students of class VII SMPN 1 Koto XI Tarusan, Pesisir Selatan Regency totaling 87 people. The sampling technique used was total sampling technique. The instrument used is a questionnaire. Data analysis used percentage technique. The results of this study reveal that in general the profile of the discipline form of students in class VII SMPN 1 Koto XI Tarusan, Pesisir Selatan Regency is in the High category. Judging from each indicator: 1) The form of student discipline seen from discipline based on authoritarian concepts is in the Low category, 2) The form of student discipline seen from discipline based on permissive concepts is in the high category. 3) The form of student discipline seen from the discipline based on the concept of controlled freedom is in the very high category. Based on the findings of this study, the researcher recommends that students be able to maintain, maintain order and improve discipline.